Neonatal Myxomas: Case Report and Literature Review. Issue 6 (November 2022) - Pasternack, Daniel M; Sharma, Madhu; Colavito, John; Ramirez, Michelle M; Martinez, Michael J; Chakravarti, Sujata; Mosca, Ralph; Susheel Kumar, TK
Myxomas are rare tumors in neonates and tend to have a different presentation compared to adults. We present an infant with a left atrial myxoma presenting with episodic tachycardia who underwent successful surgical excision. In addition, we performed a review of the literature, identifying 17 cases of neonatal myxomas. Unlike adults, neonatal myxomas are more common in males and occur more often on the right side of the heart. Constitutional symptoms such as fever or embolism are rare among neonates. Most patients have favorable outcomes following surgical excision, refuting earlier claims that neonatal myxomas are associated with poor outcomes.